Pendampingan Orang Tua pada Anak Usia Dini dalam Penggunaan Teknologi Digital [Parent Mentoring of Young Children in the Use of Digital Technology] - Tesa Alia; Irwansyah Irwansyah (Universitas Pelita Harapan, 2018)
Technological advances have a significant influence on people's lives including within families. It is undeniable that the current technological advances mainly based on internet services have had both positive and negative impacts on the growth of children in the family. Children born after the 1980’s are a living generation who grew up with information technology and diverse online social applications. Electronic gadgets such as smartphones, laptops, computers, tablets, and so forth have made it easy for children to access the Internet almost anywhere and anytime. Parents play an important role in the development of early childhood communication, especially for children under the age of five. One of the efforts of parents in providing education for children in the family in the digital era is by providing assistance in the use of technology for children. Through mentoring, parents can supervise children and direct positive content for children to use technological advancements appropriately in accordance with the child's growth and development.BAHASA INDONESIA ABSTRAK: Kemajuan teknologi memberikan pengaruh signifikan terhadap kehidupan masyarakat termasuk dalam ruang lingkup keluarga. Tidak bisa dipungkiri bahwa kemajuan teknologi saat ini terutama berbasis layanan internet memberikan dampak positif dan juga dampak negatif bagi tumbuh kembang anak dalam keluarga. Anak-anak yang lahir setelah era tahun 1980-an merupakan generasi yang hidup di tengah majunya teknologi informasi dan beragam aplikasi sosial dimulai secara daring (online). Melalui gadget seperti smartphone, laptop, komputer, tablet, dan lain sebagainya memberikan kemudahan bagi anak untuk mengakses jaringan internet di mana pun dan kapan pun. Orang tua berperan penting dalam perkembangan komunikasi anak usia dini, khususnya anak di bawah usia lima tahun. Salah satu upaya orang tua dalam memberikan pendidikan bagi anak dalam keluarga di era digital seperti sekarang adalah dengan memberikan pendampingan dalam penggunaan teknologi bagi anak. Melalui pendampingan tersebut, orang tua dapat mengawasi anak dan mengarahkan konten-konten positif bagi anak untuk menggunakan kemajuan teknologi secara tepat sesuai dengan masa tumbuh kembang anak.